Reziliența rețelei școlare în România – dinamica structurilor spațiale ale școlilor primare rurale - Victoria Buza (Sociologie Românească, 2025)
Recent research into the geography of education frequently addresses the consequences of declining birth rates and demographic ageing in relation to the shrinking rural school network. Although studies often present conflicting views, whether it is pro- or anti-restructuring, the motivations of decision-makers converge around similar dilemmas: a small school is not financially sustainable, although the institution itself in a small village is perceived by the local community as the "heart of the village". However, the steady decline in school population forces decisions to close or merge them with larger ones, and implicitly, the daily commute of pupils to the larger one. The motivation for this analysis follows from an exhaustive rationale based on the scarcity of quantitative micro- and macro-scale research on the resilience of the rural school network to the dynamics of the primary-age population. The objectives of the study are aimed both at the punctual identification of the spatial structures and conjunctural situations regarding the numerical evolution of primary schools in Romania between 2015-2021, as well as the geographical and cartographic analysis of the spaces with indicators at both extremes of school population statistics. On the one hand, the areas affected early by the effects of depopulation have seen the most extensive restructuring of the schools, either by merging the small units or by adopting multi-grade teaching, one the other hand, the suburban areas of large cities have experienced substantial increases in a short period of time in the number of pupils, leading to overcrowding of classes.